Aspek Pilihan Rasional Dan Efektifitas Dalam Pembentukan Asean And China Cooperative Operations In Response To Dangerous Drugs (ACCORD) - Hidayat, Muhammad Nizar (Interdependence Journal of International Studies, 2020)
Issues on drugs abuse have become major political concern throughout the world including South East Asia (ASEAN). To tackle this issue, regional cooperation framework is urgently needed and one of the milestones of ASEAN is Bangkok Political Declaration in Pursuit of a Drug-Free ASEAN 2015 and more importantly the establishment of ASEAN and China Cooperative Operations in Response to Dangerous Drugs (ACCORD). ACCORD emerged as a regional regime to improve the previous regimes set by ASEAN. Against that backdrop, this article will try to analyze the aspect of rational choice in the establishment of ACOORD and how effective is ACCORD in tackling the issue of drugs abuse in South East Asia.